Fabrication of Non-phospholipid Liposomal Nanocarrier for Sustained-Release of the Fungicide Cymoxanil - Zhang, Zheng; Yang, Jun; Yang, Qing; Tian, Guangyong; Cui, Zhong-Kai (Frontiers in Molecular Biosciences, 2021)
Liposome nanocarriers can be used to solve problems of pesticide instability, rapid degradation and a short period of efficacy. Cymoxanil with antifungal activity requires an ideal drug loading system due to its degradation issues. In this paper, cholesterol and stearylamine were used to prepare non-phospholipid liposomes (sterosomes) as a pesticide nanocarrier, and were characterized with field emission scanning electron microscopy (FE-SEM), X-ray powder diffraction (XRD), Fourier-transform infrared (FT-IR) spectrometer, size distribution, and ζ-potential. The results showed sterosomes were successfully loaded with cymoxanil. The loading efficiency and the drug-to-lipid ratio were 92.6% and 0.0761, respectively. Prolonged drug release was obtained for 3 days, improving the short duration of the drug itself. The addition of cymoxanil-loaded sterosomes in culture medium effectively inhibited the growth of yeast cells, which serve as model fungal targets. Sterosomes as nanocarriers significantly improved the stability and efficacy of cymoxanil, thus introducing practical and economically desirable strategies for the preparation of novel pesticide formulations.